Short-term Exposure to Air Pollution and Attributable Risk of Kidney Diseases: A Nationwide Time-series Study. Issue 1 (24th November 2021) - Lee, Whanhee; Prifti, Kristi; Kim, Ho; Kim, Ejin; Yang, Juyeon; Min, Jieun; Park, Jae Yoon; Kim, Yong Chul; Lee, Jung Pyo; Bell, Michelle L.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Several studies have shown that long-term exposure to air pollution is associated with reduced kidney function. However, less is known about effects of short-term exposure to air pollution on kidney disease aggravation and resultant emergency room (ER) burden. This study aimed to estimate excess ER visits attributable to short-term air pollution and to provide evidence relevant to air pollution standards to protect kidney patients. Methods: We conducted time-series analysis using National Health Insurance data covering all persons in South Korea (2003-2013). We collected daily data for air pollutants (particulate matter ≤10 µm [PM10 ], ozone [O3 ], carbon monoxide [CO], and sulfur dioxide [SO2 ]) and ER visits for total kidney and urinary system disease, acute kidney injury (AKI), and chronic kidney disease (CKD). We performed a two-stage time-series analysis to estimate excess ER visits attributable to air pollution by first calculating estimates for each of 16 regions, and then generating an overall estimate. Results: For all kidney and urinary disease (902, 043 cases), excess ER visits attributable to air pollution existed for all pollutants studied. For AKI (76, 330 cases), we estimated the highest impact on excess ER visits from O3, while for CKD (210, 929 cases), the impacts of CO and SO2 were the highest. The associations between air pollution and kidney ER visits existed for days with air pollution concentrations below current World Health Organization guidelines. Conclusion: This study provides quantitative estimates of ER burdens attributable to air pollution. Results are consistent with the hypothesis that stricter air quality standards benefit kidney patients.